Đặc điểm địa hóa của Granat trong sa khoáng ở Tây Nguyên - Phượng, Ngô Thị; Ý, Nguyễn Viết; Dung, Phạm Thị; Lam, Trần Hồng; Hằng, Hoàng Việt (Vietnam Journal of Earth Sciences, 2008)
Geochemical characteristics of placer garents in Tay Nguyen of Viet Nam